If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n = x + -1m Reorder the terms: n = -1m + x Solving n = -1m + x Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Simplifying n = -1m + x
| 20y-95-3y=2(11y+35) | | x^3-10x^2+x+99=0 | | 5(3x+2)+5x-6= | | 5y-4=2y+2 | | 3(2x+4)+3=18 | | 5(x+2)-7=5(2x+3)-1 | | [6-3n]-3=27 | | p^2-8p*21=6 | | -3(+5)=8X+18 | | 7000x-14000(x+0.5)=595 | | -3.1+5.9+(-10)+3= | | sqrt(3m+4)=m | | 5a^2*1/6 | | 3(2x-1)+5=32 | | 5=1+2x | | 24x-7-16x+3=23x-8-15x+13 | | 4x-2(x-3)=x+12 | | 7(p+2)-4p=3p+14 | | 100y+300x*40=8400 | | 7/9*1/5*3/35 | | -1/6-6 | | -2/9*-1/4 | | [3+4x]=15 | | 100+300*40=8400 | | 21/1575 | | 2(v-3)-7=-3(-5v+1)-5u | | C/6=4 | | -4(-5w+6)-7w=5(w-5)-9 | | 2n+10=107.50 | | (-2/4)x+3=1 | | 142+2.7x=300 | | 7(n-2)-6=2n+8+n |